EOS, an Ikaros family zinc finger transcription factor, interacts with the HTLV-1 oncoprotein Tax and is downregulated in peripheral blood mononuclear cells of HTLV-1-infected individuals, irrespective of clinical statuses - Tadasuke Naito; Hiroshi Ushirogawa; Takuya Fukushima; Yuetsu Tanaka; Mineki Saito (Virology Journal, 2019)
Abstract Background EOS plays an important role in maintaining the suppressive function of regulatory T cells (Tregs), and induces a regulated transformation of Tregs into T helper-like cells, which are capable of secreting proinflammatory cytokines in response to specific inflammatory signals. Meanwhile, significant reduction in Treg activity along with production of proinflammatory cytokines has been reported in patients with HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Methods In this study, to examine whether there is an alteration in EOS expression in peripheral blood mononuclear cells (PBMCs) derived from HTLV-1-infected individuals especially HAM/TSP, we investigated the expression of HTLV-1 tax genotype, proviral load (PVL), and the mRNA expression of tax, HBZ and EOS in HTLV-1 infected individuals including adult T-cell leukemia/lymphoma (ATL), HAM/TSP, or asymptomatic carriers. The expression levels of EOS mRNA and protein in various HTLV-1-infected or uninfected human T-cell lines were also investigated. Results EOS was highly expressed at the protein level in most HTLV-1 infected T-cell lines, and was augmented after the HTLV-1 regulatory factor Tax was induced in a Tax-inducible JPX-9 cell line. Immunoprecipitation experiments demonstrated a physical interaction between EOS and the viral regulatory protein Tax, but not HBZ. Meanwhile, there was a significant decrease in EOS mRNA levels in PBMCs of HTLV-1 infected individuals irrespective of their clinical statuses. We found an inverse correlation between EOS mRNA levels and HTLV-1 PVL in ATL patients, and positive correlations between both EOS mRNA load and PVL, and EOS and HBZ mRNA load in HAM/TSP patients, whereas this correlation was not observed in other clinical statuses. Conclusions These findings suggest that both Tax and HBZ can alter the expression of EOS through undetermined mechanisms, and dysregulated expression of EOS in PBMCs of HTLV-1 infected individuals may contribute to the pathological progression of HTLV-1-associated diseases, such as ATL and HAM/TSP.